The Role of Perceived Supervisor Support in Moderating the Influence of Professional Isolation Experienced During COVID-19 Remote Work on Employee Engagement - Agopian, Lori (2021)
The primary aim of this research is to study the influence of professional isolation experienced during COVID-19 remote work on employee engagement while simultaneously studying the moderating role of perceived supervisor support on this relationship. In addition, this research study analyzes the varying need for supervisor support based on age, gender and educational level. This study utilizes the need-to-belong theory as its theoretical framework. For data collection purposes, an online questionnaire was leveraged to gather data from respondents, around the world, who experienced remote work during the COVID-19 pandemic. The present study uses SPSS statistical software to investigate the relationship between the different variables. The study finds that although employee engagement may not be a function of professional isolation, for remote workers who have high levels of professional isolation, nevertheless, when supervisor support is high, employee engagement levels tend to be high too. The study recommends that organizations empower supervisors in supporting and guiding their teams virtually during times of crisis. Finally, this study recommends future research to tackle the topic in cultural context and considering additional control variables.